A retrospective review of postgraduate physiotherapy research at the University of Zambia - Loveness A. Nkhata; Margaret M. Mweshi (Rehabilitation Advances in Developing Health Systems)
Background: Highly qualified researchers are vital in rehabilitation sciences, and postgraduate physiotherapy students play a key role through their research, which bridges theoretical knowledge and practical application to enhance both education and patient care.